Global consumers and in-store promotions - Schultz, Don E. (Henry Stewart Talks, 2013)
What is in-store-sales promotion?, Reason for discussion, Varying retail approaches and cultures around the world, Planning from a customer, not a marketer’s view, Customer influences: external and internal, Comparing U.S. and Chinese consumer responses, External media consumption, i.e. time and influence, In-store promotion: vary by product category and country, New factor: rise of social media, Dynamic systems compound measurement and evaluation issues, Networks and synergy are critical for understanding